2014
DOI: 10.1002/2014ja020049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of energetic electron intensities outside and inside the radiation belts

Abstract: The intensities of energetic electrons (~25-800 keV) outside and inside Earth's radiation belts are reported using measurements from Time History of Events and Macroscale Interactions during Substorms and Van Allen Probes during nongeomagnetic storm periods. Three intervals of current disruption/dipolarization events in August 2013 were selected for comparison. The following results are obtained. (1) Phase space densities (PSDs) for the equatorially mirroring electron population at three values of the first ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Therefore, magnetic moments ( μ ) are conserved and of course the μ uc of injected electrons at different L shells are equal. Recently, based on multisatellite observations from THEMIS, Lui () and Lui et al (, ) demonstrated that the source strength of energetic electrons associated with dipolarization at the outer radiation belt boundary during both quiet and storm periods is adequate to account for the electron intensity in the outer radiation belt, if electrons could be transported inward without significant loss. Therefore, it is possible that injected electrons observed in the inner magnetosphere come from higher L shells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, magnetic moments ( μ ) are conserved and of course the μ uc of injected electrons at different L shells are equal. Recently, based on multisatellite observations from THEMIS, Lui () and Lui et al (, ) demonstrated that the source strength of energetic electrons associated with dipolarization at the outer radiation belt boundary during both quiet and storm periods is adequate to account for the electron intensity in the outer radiation belt, if electrons could be transported inward without significant loss. Therefore, it is possible that injected electrons observed in the inner magnetosphere come from higher L shells.…”
Section: Discussionmentioning
confidence: 99%
“…At even larger distances, however, it becomes too small to be detected. The relationship between radial location of the injections and geomagnetic activity was also studied (e.g., Gabrielse et al, 2014;Lopez et al, 1990;Mauk & Mcilwain, 1974). Statistically, injections can reach lower L shells with increased geomagnetic activities.…”
Section: 1002/2018ja025185mentioning
confidence: 99%